Pengaruh Kepemimpinan Dan Employee Empowerment Terhadap Kinerja Karyawan Melalui Kepuasan Kerja Sebagai Variabel Intervening Pada PT. Star Rubber Muaro Bungo Jambi - Fitriyani; Dori Mittra Candana; Mardhatila Fitri Sopali (GLOBAL SCIENTS PUBLISHER, 2026)
This study aims to analyze the effect of leadership and employee empowerment on employee performance through job satisfaction as an intervening variable at PT. Star Rubber Muaro Bungo, Jambi. This research uses a quantitative approach with data collected through questionnaires distributed to employees of PT. Star Rubber Muaro Bungo, Jambi. Data analysis was conducted using Structural Equation Modeling (SEM) with the Partial Least Square (PLS) approach. The results indicate that leadership has a positive and significant effect on job satisfaction and employee performance, employee empowerment has a positive and significant effect on job satisfaction and employee performance, and job satisfaction has a positive and significant effect on employee performance. Furthermore, job satisfaction is able to mediate the effect of leadership and employee empowerment on employee performance. Therefore, improving employee performance can be achieved through the implementation of effective leadership and optimal employee empowerment by paying attention to employee job satisfaction.